The Effect of Simvastatin and Virgin Coconut Oil (VCO) Combination Therapy as Triglyceride Plasma Lowering Agent in White Dyslipidemic Male Rat (Rattus norvegicus) - Jefferson Caesario; Soebagijo Adi; Ema Qurnianingsih (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Dyslipidemia is a major health problem in Indonesia which leads to other diseases. Triglycerides (TG) is one of the increased lipid fractions which is related to dyslipidemia. Simvastatin is the main therapy in Indonesia to lower TG levels. The use of virgin coconut oil (VCO) becomes popular as a blood cholesterol-lowering agent even though the effects on TG level remains elusive. Since there is no empirical evidence VCO as a complementary therapy of simvastatin on TG levels, this experimental trial is conducted to determine the effect of simvastatin and VCO combination therapy on blood TG levels in dyslipidemic male white rats.Methods: 42 white rats (Rattus norvegicus) divided into 5 treatment groups and preliminary test of dyslipidemia. The blood was collected intracardially and TG level was measured by using spectrophotometric methods. Independent variables are simvastatin and VCO and combination therapy while the dependent variable is TG levels of white rats. The data was afterwards analyzed using Mann-Whitney U test.Results: The control group’s triglyceride plasma level, receiving standard diet, is 59±13,4 mg/dl. The VCO-only group shows 72±35,4 mg/dl while simvastatin-only group shows 61,9±22,6 mg/dl triglyceride level. Combination therapy of simvastatin and VCO shows 62,3±31,3 mg/dl (p>0,05).Conclusion: There were no significant differences between groups with control. However,the use of VCO with particular dose and duration of therapy, will significantly decrease triglyceride level in the blood as effective as simvastatin. VCO has no efficacy while used as combination therapy of simvastatin.